1984
DOI: 10.1016/0014-5793(84)81324-1
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of actin and vimentin by calpain II, a Ca2+‐dependent cysteine proteinase, in bovine lens

Abstract: Calpain II, a high Ca2+‐requiring form of Ca2+‐dependent cysteine proteinase (EC 3.4.22.17), isolated from bovine lens was found to cleave actin and vimentin, two major cytoskeletal elements of the lens. Polyacrylamide gel electrophoresis revealed that actin (M r 43000) was broken down through intermediary products of approximate M r 42000 and 40000, while vimentin (M r 57000) was rapidly cleaved into several fragments ranging from M r 44000 to 20000. The cleavage was dependent on Ca2+ and could be blocked by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
28
0
1

Year Published

1996
1996
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 17 publications
2
28
0
1
Order By: Relevance
“…Those individual cells that appeared rounded (i.e., abnormal) stained more brightly with calpain antibody, suggesting that this was attributable to less effective calpain inhibition. A number of studies in different models ranging from the lens of the eye 13 to spinal cord neurons 14 have shown that calpains are important in actin remodeling, and this study extends those observations to cold preserved SEC. Yoshida 13 reported a direct effect of calpain on actin, but calpain is also active against actin-associated proteins such as talin 33 and actin-binding protein 34,35 and localizes in some models to the site on the cell membrane where these proteins are present.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Those individual cells that appeared rounded (i.e., abnormal) stained more brightly with calpain antibody, suggesting that this was attributable to less effective calpain inhibition. A number of studies in different models ranging from the lens of the eye 13 to spinal cord neurons 14 have shown that calpains are important in actin remodeling, and this study extends those observations to cold preserved SEC. Yoshida 13 reported a direct effect of calpain on actin, but calpain is also active against actin-associated proteins such as talin 33 and actin-binding protein 34,35 and localizes in some models to the site on the cell membrane where these proteins are present.…”
Section: Discussionsupporting
confidence: 70%
“…11 Calpain activity has been shown to be associated with remodeling of actin. [12][13][14] Therefore, we hypothesized that exposure of SEC to cold results in the following sequence: elevated intracellular calcium concentration, increased calpain activity, and actin disassembly.…”
mentioning
confidence: 99%
“…This has raised interest in the involvement of the calcium-activated protease, calpain, in cataractogenesis. Several lens proteins have been demonstrated to be good substrates for calpain [18][19][20], activation of this protease has been shown in several models of cataract formation [21,22] and inhibition of calpain resulted in slower rate of cataract formation [23].…”
Section: Introductionmentioning
confidence: 99%
“…Both the major lens pro teins, the crystallins, and cytoskelctal proteins like vimentin, actin, spectrin and beaded fila ments are degraded by calpain resulting in fragments similar to those produced in cata ract models [9,[14][15][16]. The major gap junc tion protein, MP26, is also degraded by cal pain [17], Another fact that indicates the importance of calpain in cataract formation is the finding that calpain inhibitors, like E-64 slow the rate of cataract formation in cultured lenses as well as in the whole animal [ 18].…”
mentioning
confidence: 99%